TATA KELOLA MEDIA DIGITAL DI INDONESIA: TANTANGAN DAN PELUANG DALAM REVISI UNDANG-UNDANG PENYIARAN - itok dwi kurniawan (CV Rewang Rencang, 2024)
The purpose of this study is to examine the urgency of the Draft Law (RUU) on the Amendment of Law No.32 Year 2002 on Broadcasting, which is considered lagging behind the development of technology and media. The research method uses a normative legal approach with secondary data (literature study). Broadcasting Law is included in the list of 33 bills of National Legislation Program (Prolegnas) Priority 2021 (Prolegnas) Priority 2021 proposed by DPR. Several parties, such as KPI, the Indonesian Advertising Company Association, the Child Protection Commission, the Tobacco Control Committee, and the Civil Society Coalition, have submitted proposals that reinforce the urgency of changing the law.